EFFECT OF GIVING FERMENTED SOY BEAN HUSKS EM4 ON PROTEIN DIGESTIBILITY OF PEKING DUCKS - Syahertian, Rendy; Warisman, Warisman (Bajang Institute, 2024)
The aim of this research was to determine the effect of giving EM4 fermented soybean epidermis in feed on protein digestibility in Peking ducks. This research was carried out on Jl. Sawi, West Binjai District, Binjai City. This study used a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments given were as follows: P0: basal ration (ducks without soybean epidermis), P1: 98% basal ration + 2% soybean epidermis, P2: 96% basal ration + 4% soybean epidermis, P3: 94% basal ration + giving 6% soybeans epidermis and P4: 92% basal ration + giving 8% soybeans epidermis. Observation parameters carried out included: Protein Consumption, Protein Digestibility, Nitrogen Consumption, Nitrogen Retention. The results of the research after statistical analysis showed that the treatment of giving soybean husks fermented with EM4 in feed had no significant effect on protein consumption, protein digestibility, nitrogen consumption and nitrogen retention.